Beyond Kinship Social and material reproduction in house societies - Joyce, Rosemary A.; Cunningham, Clark E.; Gillespie, Susan D. (Philadelphia, Pa. : University of Pennsylvania Press, 2000)
Clark E. Cunningham. Foreword
1. Susan G. Gillespie. Beyond kinship : an introduction
2. Susan D. Gillespie. Lévi-Strauss : Maison et société à maison
3. Alan R. Sandstom. Toponynic groups and house organization : the Nahuas of northern Veracruz, Mexico
4. Yvonne Marshall. Transformations of Nuu-chah-nulth houses
5. Patrick V. Kirch. Temples as "holy houses" : the transformation of ritual architecture in traditional polynesian societies
6. Ruth Tringham. The continuous house : A view from deep past
7. Susan D. Gillespie. Maya "nested houses" : the ritual construction of place
8. Susan McKinnon. The tanimbarese tavu : the ideology of growth and the material configurations of houses and hierarchy in an indonesian society
9. Roxana Waterson. House, place and memory in Tana Toraja (Indonesia)
10. Rosemary A. Joyce. Heirlooms and houses : materiality and social memory
Notes, bibliogr., index
0001